The Influence of UGC and Influencer Marketing on Consumer Buying Interest: A Case Study of Warunk Juragan - Natasya Sanika Putri Nasution; Nindya Yunita; Hesti Sabrina (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study explores the influence of UGC and Influencer Marketing on consumer buying interest, with a focus on Warunk Juragan in Pangkalan Masyhur Village, Medan Johor. A quantitative approach was employed, involving 99 respondents aged 15 to 44, determined using the Slovin formula from a population of 10,439 residents in 2024. Data were collected through a questionnaire and analyzed using multiple linear regression. The study demonstrates that both UGC and Influencer Marketing exert a positive and significant influence on consumer purchase intention. This indicates that content created by users and promotional efforts by influencers can effectively shape consumer decisions, emphasizing the importance of digital engagement strategies. However, despite their statistical significance, the practical impact of these approaches may be limited if not properly aligned with consumer preferences. For businesses such as Warunk Juragan, this highlights the necessity of customizing digital marketing efforts to resonate with their target audience. Practically, this involves enhancing content authenticity and choosing influencers whose personal brand aligns with the company's values. Theoretically, the findings affirm the importance of trust, social validation, and credibility in influencing online consumer behavior, offering valuable insights for SMEs aiming to strengthen engagement and boost buying interest through social media.Keywords: Consumer Buying Interest Influencer Marketing, UGC.